Above the Clouds. Issue 2 (18th September 2019) - Schmidt, Jörg; Wendisch, Manfred; Curtius, Joachim; Scheinert, Mirko; Sinnhuber, Björn‐Martin
Abstract: Taking to the skies to study the atmosphere, climate and planet: Funded by a consortium of major German research institutes, HALO has quickly become the most advanced research aircraft in Europe. With an array of modern and variable equipment, it can be used for demanding measurement campaigns from aerosol particles to air pollutants and clouds.